Asuhan Keperawatan Gangguan Integritas Kulit Pasien Diabetes Melitus Tipe II: Studi Kasus RSUD M. Thomsen Nias - Mastina Titi Jayasari Giawa; Heppynus Telaumbanua; Sunarti Sunarti (Universitas Nurul Jadid, 2026)
Type II diabetes mellitus is a chronic metabolic disease that may cause hyperglycemia and impaired peripheral tissue integrity. This case study aimed to describe nursing care for one patient with type II diabetes mellitus in the Alamanda Room of RSUD dr. M. Thomsen Nias. A descriptive case study design was applied using the nursing process framework. Data were collected through interviews, observation, physical examination, laboratory documentation, medical record review, nursing assessment format, observation sheet, and SOAP evaluation format. The case involved one 46-year-old male patient with severe hyperglycemia and signs of impaired skin integrity. Assessment showed random blood glucose of 405 mg/dL, fasting blood glucose of 404 mg/dL, HbA1c of 14.8%, leukocytosis, and erythematous peeling skin on the lower extremity. The main nursing diagnoses were unstable blood glucose level, impaired skin/tissue integrity related to circulatory and metabolic changes due to hyperglycemia, and fatigue. Interventions included hyperglycemia management, blood glucose monitoring, diabetic diet education, insulin collaboration, sterile skin care, infection monitoring, activity-rest education, discharge planning, and family involvement. Short-term clinical improvement was observed over three days, but blood glucose remained high at 280 mg/dL; therefore, continued care and self-management education are required.